Reaching the Marginalized: Do Education Expenditure and Other Indicators AlleviatePoverty in the Philippines - Nuñez, Sofia Mae; Aguado, Reign Christine; Barua, Jaira Mei; Capariño, Charisse Mae (Social Sciences and Development Review, 2024)
This study examines if government expenditure and other indicators alleviate poverty in the Philippines. This study employs time series data of unemployment rate, business confidence, and education expenditures from 2001-2022, making it to 21 observations. In this paper, several tests are used, namely Augmented Dickey-Fuller (ADF) for stationarity, Breusch Godfrey Serial Correlation LM Test, Variance Inflation Factor (VIF) for autocorrelation and multicollinearity. The Johansen Cointegration and the Pairwise Granger Causality Test were also performed to find out if there is a long-run relationship and causality between the variables. The results reveal that there is a long-run relationship and bidirectional causality between unemployment and poverty, also there is a longrun relationship but unidirectional causality between business confidence and poverty, while the education expenditures and poverty show no long-run relationship under the Johansen cointegration test and no causality under the Granger causality test. The findings suggest that policymakers should provide more job opportunities, enhance support for entrepreneurship, and allocate budgets for education properly to enhance the quality of education and ensure access for all.
Keywords: Business Confidence; Education Expenditure; Government Expenditure; Unemployment; Poverty